Evaluation of Hospital Management Information System (HMIS) Implementation on Administrative Service Efficiency - Violent Andary; Dwi Ris Hasanah SI (Journal of Innovative and Creativity, 2026)
Background: Hospital Management Information Systems (HMIS) are increasingly recognized as essential tools for improving administrative efficiency in healthcare settings. Rumah Sakit Islam Malahayati (RSI Malahayati) in Medan, Indonesia adopted an integrated HMIS to streamline its administrative processes; however, the extent to which the system has effectively improved service delivery efficiency remains inadequately evaluated. This study aimed to evaluate the implementation of HMIS on administrative service efficiency at RSI Malahayati, Medan, in 2026. Methods: A qualitative study employing a phenomenological approach guided by the Colaizzi method was conducted from September to December 2025. The study was set at RSI Malahayati, a 150-bed Islamic private hospital in Medan, North Sumatra. Purposive sampling was applied to recruit 18 participants, including hospital administrators, information technology staff, medical records officers, and front-line administrative personnel. Inclusion criteria required direct engagement with HMIS for a minimum of six months. In-depth, semi-structured interviews were conducted face-to-face, averaging 55 minutes per session. Interviews were audio-recorded, transcribed verbatim, and analyzed using NVivo 12 software. Data saturation was confirmed at the 16th interview. Trustworthiness was ensured through triangulation, member checking, and peer debriefing, in conformity with COREQ standards. Results: Four major themes emerged from data analysis: (1) Enhanced administrative workflow integration, characterized by reduced manual data entry and inter-departmental communication delays; (2) Barriers to optimal system utilization, encompassing inadequate technical training, system downtime incidents, and user resistance; (3) Impact on patient service responsiveness, reflecting shorter waiting times and improved patient registration accuracy; and (4) Organizational and cultural factors shaping HMIS adoption, including leadership support and Islamic institutional values influencing staff acceptance. Participants consistently acknowledged improvements in data accuracy and reporting efficiency, though persistent technical and human resource challenges limited system performance. Conclusion: HMIS implementation at RSI Malahayati has demonstrably improved administrative service efficiency through enhanced workflow integration and data management. However, sustainable efficiency gains require addressing identified barriers through comprehensive staff training, technical infrastructure reinforcement, and culturally responsive change management strategies tailored to Islamic hospital settings.